Linking the genetic diversity of root traits and drought responses in wild Vitis species - E.R. Patin; U. Pérez-López; A. del Sol Iturralde; J. Valls-Fonayet; P. Pétriacq; P. Gastou; J.P. Tandonnet; M. Larrey; P. Vivin; E. Marguerit; N. Ollat; M. de Miguel (Plant Stress)
Drought impacts viticulture reducing yield, and grape and wine quality. Roots play a key role in maintaining water status both through constitutive traits and through morphological, physiological and biochemical adjustments in response to drought. For this reason, the root system is a novel target in crop breeding programs aiming to produce drought adapted varieties. However, the relationships between roots traits and drought responses in perennial crops are poorly known. To address this, we aimed to link root syndromes of genetically controlled traits with genetic variation of shoot drought responses across a previously unexplored range of wild Vitis species. We identified three constitutive root syndromes that partially explained shoot drought responses. The first root syndrome had root systems with few ramifications, the second syndrome had a higher number of adventitious roots and thicker ramifications, and third syndrome was characterized by higher root biomass and higher cumulative root length. Those genotypes of the first and second syndrome had higher stem elongation rates and transpiration during early stages of the drought treatment compared to the third one. The accessions associated with the first syndrome were North American Vitis species, those with the second syndrome mostly the Eurasian V. sylvestris, and those associated with the third syndrome were two Asian species and the North American species V. labrusca. We also explored genetic variation in root functional trait plasticity in response to drought. Notably, two North American species, V. acerifolia and V. doaniana, showed high osmotic adjustment, while Asian species showed high plasticity in polyphenol concentrations. The originality of this work lies in the evaluation of root traits in previously uncharacterized Vitis accessions and the identification of constitutive root syndromes that could aid in the selection of more drought adapted rootstocks.